2015
DOI: 10.1111/bjd.13953
|View full text |Cite
|
Sign up to set email alerts
|

Lower‐extremity ulcers: diagnosis and management

Abstract: Chronic wounds of the lower extremities are occurring with increasing prevalence. They affect millions of individuals annually, representing both a significant health risk and a large economic burden. Chronic wounds are associated with increased mortality and substantial morbidity due to infection, pain, limitation of daily activities, and psychosocial consequences. To manage these wounds effectively, clinicians must be able to diagnose and manage their aetiology. Diagnosis starts with determining whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 93 publications
1
93
0
2
Order By: Relevance
“…25,26 The lowest value is seen on anterior pretibial, it can attribute to the fact that the blood supply is lack of arteriovenous shunt, which can explain why wounds on the lower leg heal more slowly than elsewhere. 27 Our results show a tendency that perfusion values are higher in men than women, the difference can be seen on bank of fingertips, nose, forehead, cheek, neck, and earlobe, which is similar to some preceding researches. [28][29][30] There are several possible explanations, Goldberg J held the view that epidermis in female was thinner seemed most plausible.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…25,26 The lowest value is seen on anterior pretibial, it can attribute to the fact that the blood supply is lack of arteriovenous shunt, which can explain why wounds on the lower leg heal more slowly than elsewhere. 27 Our results show a tendency that perfusion values are higher in men than women, the difference can be seen on bank of fingertips, nose, forehead, cheek, neck, and earlobe, which is similar to some preceding researches. [28][29][30] There are several possible explanations, Goldberg J held the view that epidermis in female was thinner seemed most plausible.…”
Section: Discussionsupporting
confidence: 91%
“…It may partly attribute to the distributional or functional differences in cutaneous appendages such as sebaceous glands and sweat glands . The lowest value is seen on anterior pretibial, it can attribute to the fact that the blood supply is lack of arteriovenous shunt, which can explain why wounds on the lower leg heal more slowly than elsewhere …”
Section: Discussionmentioning
confidence: 99%
“…In addition to ankle brachial index (ABI) values, the Fontaine classification system was used to classify the severity of PAD. 27-30 Clinical manifestations of PAD ranged from moderate to severe intermittent claudication in conjunction with minor tissue loss and nonhealing ulcerations. The classification of a wound as recalcitrant depended on a minimum previous treatment duration of ≥120 days (4 months) characterized by a prior failure to respond SOC and ≥1 advanced therapy regimens.…”
Section: Methodsmentioning
confidence: 99%
“…Kirsner 10 identified that application of compression on the limb can minimize or reverse venous reflux caused by valve incompetence, forcing fluid present in the interstitial spaces to return to the vascular and lymphatic systems, thus reducing tissue edema. However, this solution is temporary and would work only while the patient is wearing the compressive device, implying in the use of elastic stockings even after the ulcer has healed.…”
Section: Treatment Optionsmentioning
confidence: 99%